Prognostic Influence of Residual Tumor-Infiltrating Lymphocyte Subtype After Neoadjuvant Chemotherapy in Triple-Negative Breast Cancer - da Silva, Jesse Lopes; de Albuquerque, Lucas Zanetti; Rodrigues, Fabiana Resende; de Mesquita, Guilherme Gomes; Fernandes, Priscila Valverde; Thuler, Luiz Claudio Santos; de Melo, Andreia Cristina (Frontiers in Oncology, 2021)
Objective: This study aimed to examine the prevalence and prognostic role of tumor microenvironment (TME) in triple-negative breast cancer (TNBC) after neoadjuvant chemotherapy (NACT) through immunohistochemical characterization. Methods: The internal database of the Brazilian National Cancer Institute for women diagnosed with TNBC who underwent NACT and thereafter curative surgery between January 2010 and December 2014 was queried out. Core biopsy specimens and tissue microarrays containing surgical samples of TNBC from 171 and 134 women, respectively, were assessed by immunohistochemistry for CD3, CD4, CD8, CD 14, CD 56, CD 68, CD 117, FOXP3, PD-1, PD- L1, and PD-L2. Immune cell profiles were analyzed and correlated with response and survival. Results: Mean age was 50.5 years, and most cases were clinical stage III [143 cases (83.6%)]. According to the multivariate analysis, only Ki67 and clinical stage significantly influenced the pattern of response to systemic treatment (p = 0.019 and p = 0.033, respectively). None of the pre-NACT IHC markers showed a significant association with event-free survival (EFS) or overall survival (OS). As for post-NACT markers, patients with high CD14 had significantly shorter EFS (p = 0.015), while patients with high CD3 (p = 0.025), CD4 (p = 0.025), CD8 (p = 0.030), CD14 (p = 0.015), FOXP3 (p = 0.005), high ratios CD4/FOXP3 (p = 0.034) and CD8/FOXP3 (p = 0.008), showed longer EFS. Only high post-NACT CD4 showed significantly influenced OS (p = 0.038). Conclusion: The present study demonstrated that the post-NACT TILs subtype can be a determining factor in the prognosis of patients with TNBC.